2023
DOI: 10.1186/s10020-023-00694-7
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase P300 deficiency promotes ferroptosis of vascular smooth muscle cells by activating the HIF-1α/HMOX1 axis

Abstract: Background E1A-associated 300-kDa protein (P300), an endogenous histone acetyltransferase, contributes to modifications of the chromatin landscape of genes involved in multiple cardiovascular diseases. Ferroptosis of vascular smooth muscle cells (VSMCs) is a novel pathological mechanism of aortic dissection. However, whether P300 regulates VSMC ferroptosis remains unknown. Methods Cystine deprivation (CD) and imidazole ketone erastin (IKE) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In vitro experiments verified that classical ferroptosis inhibitor liproxstatin-1 could suppress the expression of HO-1 in H 2 O 2 -induced ferroptosis model. Our findings were in line with previous in vitro experiments, which demonstrated that HO-1 was overexpressed in both cystine deprivation and imidazole ketone erastin induced VSMC ferroptosis models [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In vitro experiments verified that classical ferroptosis inhibitor liproxstatin-1 could suppress the expression of HO-1 in H 2 O 2 -induced ferroptosis model. Our findings were in line with previous in vitro experiments, which demonstrated that HO-1 was overexpressed in both cystine deprivation and imidazole ketone erastin induced VSMC ferroptosis models [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Over the decades, HIF-1α has been proved to be induced under hypoxia, oxidative stress and other transient stimulus [ 53 ]. Although its overexpression has already been identified in several literatures on ATAAD [ 45 , 54 , 55 ], molecular mechanisms of how HIF-1α promotes dissection progression remain still little known. Here, we have demonstrated a novel mechanism of VSMC ferroptosis through HIF-1α/HO-1 axis in response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…2I), pitstop2 (42) (clathrin-mediated endocytosis inhibitor, Supplemental Fig. 2J), EML425 and C646 (43) (p300/CBP Inhibitor, Supplemental Fig. 2K-L), brequinar (44) (dihydroorotate dehydrogenase (DHODH) inhibitors, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that bilirubin or biliverdin and carbon monoxide, which are metabolites of HO1, can reduce oxidative stress and inhibit ferroptosis (Ryter et al 2006 ; Sugimoto et al 2012 ). However, ferrous ions produced during HO1 metabolism can promote ferroptosis (Papanikolaou and Pantopoulos 2005 ; Shi et al 2023 ). In our study, the change in HO1 expression was synchronized with SIRT1 and GPX4, and ferroptosis was inhibited.…”
Section: Discussionmentioning
confidence: 99%